Protoporphyrin IX for photodynamic therapy of brain tumours - Johansson, A.; Kreth, F. W.; Ardeshiri, A.; Stummer, W.; Schnell, Oliver; Herms, J.; Palte, G.; Beyer, W.; Stepp, H. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2010)
Protoporphyrin IX (PpIX) displays high tumour-selective uptake following oral administration of 5-aminolaevulinic acid (ALA), a fact that is being exploited for the fluorescence-guided resection (FGR) and photodynamic therapy (PDT) of human brain malignancies. A clinical procedure for interstitial PDT (iPDT) has been established including pre-treatment planning, optical fiber insertion under stereotactic guidance and therapeutic irradiation at non-thermal fluence rates. We have previously reported on median survival in the range of 15 months and the existence of some intriguing long-term survivors (>5 years) following iPDT. Such successful treatments rely on for example sufficient light, PpIX and oxygen levels. We have investigated the absolute PpIX concentration as well as the PDT-induced photobleaching kinetics in brain tissues. Tissue samples acquired during FGR contained PpIX concentrations up to 28 μM. This observation implies that ALA-induced PpIX levels are sufficient for inducing PDT effects in viable tumour tissue upon therapeutic irradiation. However, regions of pre-existing necrosis were characterised by significantly lower photosensitiser levels. Fluorescence spectroscopy was implemented in parallel to iPDT with the aim to employ PpIX photobleaching as a tool for realtime treatment supervision and early treatment prognosis. ©2010 SPIE.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Brain; Dosimetry; Fluorescence; Interstitial; Photobleaching; Photodynamic therapy; PpIX